Applied Theatre for Workplace Conflict Resolution in UAE - Mansour, Lilas Ryad (2025)
A Master of Business Administration (MBA) thesis by Lilas Ryad Mansour entitled, “Applied Theatre for Workplace Conflict Resolution in UAE”, submitted in April 2025. Thesis advisor is Dr. Omar Belkhouja. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).